(untitled) (Environment & Health, 2020)
The current radiation and environmental situation in the raions of Kyiv oblast the most affected the Chornobyl nuclear power plant accident indicates that there is a necessity to continue monitoring levels of radioactive contamination of foods of forest origin, as well as incorporated 137Cs concentrations in the residents of these areas. The children’s population have a higher radiosensitivity and it should be the prior monitored group. Objective: We analyzed the dynamics of137Cs concentrations in children residing in Ivankiv and Polissia raions, Kyiv oblast, taking into account their age and gender and the implementation of the radiation safety programme foreseen by the European Commission project. Material and methods: Radiometric, mathematical and statistical methods. Results:10,392 SHI measurements of radionuclide levels in children aged 0-18 years were conducted during 2014-2017. Cases with relatively low median values for 137Cs specific activity in the organism was an average of 95.0 %, including in the groups of boys and girlsThe critical group included children with radiocaesium levels over 5.0 Bq/kg. The highest concentrations of 137Cs in children were reported in October - January, i.e. during the period of intensive harvesting and consumption of mushrooms. In dynamicsof 2014-2017, the probably high specific activity of radiocaesium was found in the children aged 6.0-11.0 years in comparison with the age group of 12.0-18.0 years. The maximum value of 137Cs specific activity in a child’s organism (307.29 Bq/kg) was recorded in 2014-2015. Informing the population of Ivankiv and Polissia raions on radiation safety allowed to halve the proportion of 137Cs radionuclides in the organism (over 5.0 Bq / kg) in the examined group of children.